Narrative Study on Teachers’ Strategy to Teach Oral Communicative Competences during Pandemics - Deni Subana Arya Andika Azmin; Endang Susilawati; Ikhsanudin Ikhsanudin (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
Covid-19 has caused changes in teachers’ strategies in teaching English as a Foreign Language. In teaching oral communicative competence, it is harder for English teacher to select the most suitable teaching strategy. The implementation of online learning during the pandemic is one of the alternatives that have been taken among English teacher in Indonesia. This study was conducted to find out the teachers’ strategies in teaching oral communicative competence of senior high school student during the pandemics. By utilizing narrative inquiry like interview and narrative frame as the data collection method, the researcher sought to investigate the teachers’ strategies in teaching English oral communicative competence in SMAN 3 Pontianak. The data from the participants’ story and interview transcriptions was analyzed by using thematic analysis. Based on the result findings, it is concluded that the teacher has implemented various kind of teaching strategies to teach oral communicative competence during pandemics that includes selecting suitable online platform, initiating an effective learning modes and implementing different kind of teaching method. Using narrative research design, this present study was conducted to comprehensively understand teachers' strategies to improve students' oral communicative competence based on the teacher's stories throughout their teaching experiences during pandemics.